Genome‐wide DNA methylation profiling shows molecular heterogeneity of anaplastic pleomorphic xanthoastrocytoma. Issue 2 (4th January 2019) - Nakamura, Taishi; Fukuoka, Kohei; Nakano, Yoshiko; Yamasaki, Kai; Matsushita, Yuko; Yamashita, Satoshi; Ikeda, Junji; Udaka, Naoko; Tanoshima, Reo; Shiba, Norio; Tateishi, Kensuke; Yamanaka, Shoji; et al.
Abstract : In the revised World Health Organization classification 2016, anaplastic pleomorphic xanthoastrocytoma (PXA) has been newly defined as a variant of the PXA entity. Furthermore, some anaplastic PXA were reported to have extremely poor prognosis which showed a type of pediatric glioblastoma (GBM) molecular profile. Recent integrated molecular classification for primary central nervous system tumors proposed some differences between histological and molecular features. Herein, in a genome‐wide molecular analysis, we show an extreme aggressive anaplastic PXA that resulted in a pediatric GBM molecular profile. A full implementation of the molecular approach is the key to predict prognosis and decide the treatment strategy for anaplastic PXA. Abstract : This report suggests that anaplastic PXA consists of clinically and biologically distinct multiple entities, and genome‐wide molecular profiling may help to identify them. This new approach will be useful for predicting prognosis and choosing treatment for anaplastic PXA patients.